123I metaiodobenzylguanidine (MIBG) scintigraphy of retinoblastoma: preliminary experience. Issue 2 (February 1989) - Bomanji, J; Hungerford, J L; Kingston, J E; Levison, D A; Britton, K E
Abstract : 123I metaiodobenzylguanidine (MIBG) is a radiopharmaceutical used for imaging neural crest tumours. The possibility of using 123I MIBG for imaging retinoblastomas has been assessed in this pilot study. Ten patients were studied, nine with clinically and histologically proved retinoblastomas and one with Coats's disease. 123I MIBG scintigraphy correctly identified the neoplasm in eight patients but gave a negative result in two, one of whom had Coats's disease and the other a retinoblastoma which proved to be extensively necrotic on histological examination. These preliminary results suggest that 123I MIBG scintigraphy may have a role in differentiating retinoblastomas from lesions that simulate them.